MULTICULTURAL ASPECT OF HIGHER UKRAINE EDUCATION IN THE PROCESS OF INTEGRATION - Барановська, Л. В.; Барановський, М. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
In the article it is  defined the features of native system of higher education orientation in Evrointegration’s conditions. It operates on the basis of European multicultural educational space  principles